Germ Cell Transplantation in Felids: A Potential Approach to Preserving Endangered Species - Silva, Robson C.; Costa, Guilherme M. J.; Lacerda, Samyra M. S. N.; Batlouni, Sergio R. [UNESP]; Soares, Jaqueline M.; Avelar, Gleide F.; Boettger, Karin B.; Silva, Silverio F.; Nogueira, Maria S.; Andrade, Leonardo M.; Franca, Luiz R. (Amer Soc Andrology, Inc, 2012)
With the exception of the domestic cat, all members of the family Felidae are considered either endangered or threatened. Although not yet used for this purpose, spermatogonial stem cell (SSC) transplantation has a high potential to preserve the genetic stock of endangered species. However, this technique has not previously been established in felids. Therefore, we developed the necessary procedures to perform syngeneic and xenogeneic SSC transplants (eg, germ cell [GC] depletion in the recipient domestic cats, enrichment and labeling of donor cell suspension, and the transplantation method) in order to investigate the feasibility of the domestic cat as a recipient for the preservation and propagation of male germ plasm from wild felids. In comparison with busulfan treatment, local x-ray fractionated radiation was a more effective approach to depleting endogenous spermatogenesis. The results of both syngeneic and xenogeneic transplants revealed that SSCs were able to successfully colonize and differentiate in the recipient testis, generating elongated spermatids several weeks posttransplantation. Specifically, ocelot spermatozoa were observed in the cat epididymis 13 weeks following transplantation. As donor GCs from domestic cats and ocelots were able to develop and form mature GCs in the recipient environment seminiferous tubules, these findings indicate that the domestic cat is a suitable recipient for SSC transplantation. Moreover, as modern cats descended from a medium-size cat that existed approximately 10 to 11 million years ago, these results strongly suggest that the domestic cat could be potentially used as a recipient for generating and propagating the genome of wild felids.
Keywords: Testis; x-ray radiation; spermatogonial stem cell transplantation; busulfan treatment; domestic cat (Felis catus); ocelot (Leopardus pardalis)